SCARECROW is deployed in distinct contexts during rice and maize leaf development - Hughes, T.E (NLM (Medline), 2022)
The flexible deployment of developmental regulators is an increasingly appreciated aspect of plant development and evolution. The GRAS transcription factor SCARECROW (SCR) regulates the development of the endodermis in Arabidopsis and maize roots, but during leaf development it regulates the development of distinct cell types; bundle-sheath in Arabidopsis and mesophyll in maize. In rice, SCR is implicated in stomatal patterning, but it is unknown whether this function is additional to a role in inner leaf patterning. Here, we demonstrate that two duplicated SCR genes function redundantly in rice. Contrary to previous reports, we show that these genes are necessary for stomatal development, with stomata virtually absent from leaves that are initiated after germination of mutants. The stomatal regulator OsMUTE is downregulated in Osscr1;Osscr2 mutants, indicating that OsSCR acts early in stomatal development. Notably, Osscr1;Osscr2 mutants do not exhibit the inner leaf patterning perturbations seen in Zmscr1;Zmscr1h mutants, and Zmscr1;Zmscr1h mutants do not exhibit major perturbations in stomatal patterning. Taken together, these results indicate that SCR was deployed in different developmental contexts after the divergence of rice and maize around 50 million years ago. © 2022. Published by The Company of Biologists Ltd.